ID: 170. Issue 1 (November 2015) - Stacey, Maria A.; Clare, Simon; Marsden, Morgan; Clement, Mathew; Fielding, Ceri A.; Johnson, Zoë; Ferlin, Walter; Jones, Simon A.; Kellam, Paul; Humphreys, Ian R.
<x xml:space="preserve">Abstract</x> The antiviral restriction factor interferon-induced transmembrane protein 3 (IFITM3) inhibits endocytosis-dependent entry of numerous viruses and determines susceptible to viral disease in humans. Using the murine cytomegalovirus (MCMV) model, we discovered that regulation of pro-inflammatory cytokine production is a critical function of IFITM3. IFITM3 prevented MCMV-induced weight loss and death without directly restricting MCMV replication. Instead, susceptibility of IFITM3−/− mice was attributed to an enhanced MCMV-induced lymphopenia, activation-induced NK cell death and impaired T cell responses, resulting in uncontrolled virus replication. Exacerbated pathology in IFITM3−/− mice was associated with increased expression of the pro-inflammatory cytokine interleukin-6 (IL-6), and IFITM3 exerted cell-intrinsic inhibition of MCMV-induced IL-6 expression by myeloid cells. Although IL-6 is required for the generation of antiviral adaptive immunity, inhibiting anti-IL-6R reversed MCMV-induced pathology and control of early MCMV replication. These data suggest that IFITM3 restricts viral pathogenesis, at least in part, via regulation of pro-inflammatory cytokine production.